Faktor-faktor yang Mempengaruhi Minat Siswa dalam Pembelajaran Tari pada Ekstrakurikuler di SMA Adabiah Padang - Novita Armela; Darmawati Darmawati (Journal of Creative Student Research, 2024)
This study aims to find out what are the factors that affect students' interest in learning dance in extracurricular activities at Adabiah Padang High School. This type of research is qualitative research with a descriptive method. The research instrument is the researcher himself and is assisted by supporting instruments such as stationery and cameras. Data were collected through literature studies, observations, interviews and documentation. The steps to analyze data are data collection, data reduction, data presentation and conclusion drawn. The results of the study show that the factors that affect students' interest in learning dance in dance extracurricular at Adabiah Padang High School consist of internal factors and external factors. Internal factors are students' attention to dance extracurricular materials is very good, students' attitudes towards dance extracurricular activities are good, students' ability to perform dance movements is not good and students' interest in dance extracurricular activities is good. Meanwhile, the external factors are that the dance extracurricular coordinator at Adabiah Padang High School is not good and the infrastructure at the school is relatively low.